MID (Minimal Intervention Dentistry) by Pediatric Dentist Specialist in City of Surabaya during the COVID-19 Pandemic - Ardianti Maartrina Dewi; Dimas Prasetianto Wicaksono; Betadion Rizki Sinaredi; Riska Bangkit Nastiti; Taris Fathin Luthfiani; Tasyha Firnandia Ardiana (Indonesian Dental Association, 2023)
Introduction: COVID-19 pandemic that has occurred worldwide due to the rapid spread of the SARS-CoV-2 virus requires adaptation, including in dentistry. Changes in dental care services have occurred in Indonesia, including closing practices, using PPE up to level 4, types of procedures that can be given, duration of treatment, and criteria for pediatric patients companion. Minimal Intervention Dentistry (MID) is defined as a principle in dentistry that aims to maintain oral tissue and prevent the development of a more severe disease. This technique is child-friendly because it does not involve various dental instruments that tend to increase anxiety. MID also produces small amounts of aerosols resulting minimal spread of COVID-19. Objective: This study aims to raise awareness about the application of MID by pediatric dentists specialist in the city of Surabaya during the COVID-19 pandemic. Methods: The study utilized a questionnaire as the primary research instrument to gather data from a sample of 33 respondents out of a population of 60 pediatric dentists in Surabaya. The questionnaire covered various aspects, including the location and type of practice, years of practice, experience with practice closures, and data on actions taken by respondents regarding the implementation of MID measures during the pandemic. Results: Pediatric dentistry during the COVID-19 pandemic experienced a series of changes in its implementation, including closing practices for a period of several days, weeks and months, in 18.87%, 24.53%, 56.6% respectively. MID procedures have been widely used by pediatric dentists since before pandemic (80%) are fissure sealants with HVGIC ingredients (80%), Preventive Resin Restoration (82.8%), GIC restorations (83.9%), and SSC Hall Technique (77.3%). There were variations in the number of MID procedures performed by pediatric dentists the city of Surabaya during the COVID-19 pandemic, some of which had increased (26.67%), decreased (33.33%) and remained constant (40%). Conclusion: The implementation of the MID advantages in pediatric dentistry is very useful and has been applied before and during the COVID-19 pandemic and is recommended for future use.